The effect of android-based education on the knowledge increase about pregnancy discomfort and anxiety reduction in pregnant women during the COVID-19 Pandemic - Chentia Misse Issabella; Febry Heldayasari Prabandari (Alma Ata University Press, 2021)
Background: Pregnancy is a natural process experienced by a woman, during which there will be physical and psychological changes. Pregnant women may experience discomfort and change in feelings such as happy, worry and anxiety due to those changes. Currently, the whole world is suffering from the COVID-19 pandemic. This situation causes an increase of anxiety in pregnant women because of their ignorance about how to handle pregnancy discomfort. Entering the digital era 4.0, android can be utilized so that education and information can be more easily accessible. Objective: To determine the effect of android-based education in handling discomfort and reducing anxiety in pregnant women during the Covid-19 pandemic.Methods: This research employed a quasi-experimental with a control group time-series design. There were 120 pregnant women used as samples. A simple random sampling was carried out to obtain those samples which then formed into 2 groups, namely the experimental group and the control group. The instrument used were the Busevid (Healthy Pregnant Women in the COVID-19 Period) android application and a questionnaire designed by the researchers which had been evaluated by the experts and tested. Then, the Manova with GLM repeated measures was utilized to analyze the data. Results: The increased knowledge of discomfort in the android group was 43.77 in the post-test 1 and 59.98 in the post-test 2, while the leaflet group was 17.18 in the post-test 1 and 35.92 in the post-test 2. The anxiety reduction in the android group was 16.90 in post-test 1 and 28.65 in the post-test 2, while the leaflet group was 4.35 in the post-test 1 and 5.10 in the post-test 2. The p-value was 0.000 <0.05, indicating that there was an effect of android-based education on handling discomfort and reducing anxiety in pregnant women during the Covid-19 pandemic.Conclusion: Android application can provide a significant change in increasing knowledge about discomfort and decreasing anxiety in pregnant women during the Covid-19 pandemic, so that android can be used as an alternative in providing positive benefits in education media and health promotion.